Pola Pertumbuhan Ikan Peam (Leptobarbus melanopterus) di Taman Nasional Danau Sentarum Kabupaten Kapuas Hulu - Tri Rima Setyawati, Barrata Ari Hepi Yanti (Universitas Tanjungpura, 2019)
Overfishing has been being the major problem for Leptobarbus melanopterus population in Danau Sentarum National Park. This activity was feared could affect the declining of L. melanopterus population in the future. This research aims to determine growth pattern of L. melanopterus through length-weight relationship and relative weight analysis. The total of 64 fishes were collected which consisted of 32 males and 32 females. The range of male total length was 146-248 mm with weight was 40-170 gram, whereas total length female was ranging 141-299 mm with weight was 40-350 gram. Based on the regression analysis of length-weight data, the b value of male and female were estimated 2,46 and 2,81 respectively. Moreover, the b value of all samples without distinguishing sex type was 2,69 with relative weight was 101,33. The results of this research confirms that either females or males has negative allometric growth pattern.